2020
DOI: 10.1302/0301-620x.102b8.bjj-2019-1448.r1
|View full text |Cite
|
Sign up to set email alerts
|

Uncemented tantalum metal components versus cemented tibial components in total knee arthroplasty: 11- to 15-year outcomes of a single-blinded randomized controlled trial

Abstract: Aims Total knee arthroplasty is an established treatment for knee osteoarthritis with excellent long-term results, but there remains controversy about the role of uncemented prostheses. We present the long-term results of a randomized trial comparing an uncemented tantalum metal tibial component with a conventional cemented component of the same implant design. Methods Patients under the age of 70 years with symptomatic osteoarthritis of the knee were randomized to receive either an uncemented tantalum metal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…A 13-year randomized controlled trial of such a device found better patient outcomes and radiological findings compared to a conventional metal-backed design. 35 This improved performance may have been partially due to the more normal load transfer for the trabecular metal design. Our data can also be compared to computational models of load transfer in the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…A 13-year randomized controlled trial of such a device found better patient outcomes and radiological findings compared to a conventional metal-backed design. 35 This improved performance may have been partially due to the more normal load transfer for the trabecular metal design. Our data can also be compared to computational models of load transfer in the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) and total knee arthroplasty (TKA) have been proven as the [1] methods of choice in the treatment of end-stage hip or knee pathologies [2][3][4][5]. Improvement in biomaterials, surgical techniques and implant designs has been the reason for more indications for THA and TKA [1,3,4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a randomized controlled trial, a tantalum trabecular metal tibial implant had improved radiological outcome compared to a solid tibial implant over a period of 15 years. 34 Another example is that the likelihood of a complex revision is reduced if the primary implant is a low modulus all polyethylene design compared to a conventional solid metal backed design. 35 Our method builds on these findings by allowing precise control of bone strain, using a manufacturing method that has already been deployed in over 1 million knee replacement implants.…”
Section: Discussionmentioning
confidence: 99%